The Persistence of Racism in International Law: Historical Roots, Contemporary Barriers, and the Role of Global Institutions - Fraz Ashraf Khan; Uzma Khadam (Journal of Religion and Society, 2025)
This study investigates the enduring issue of racism within the context of international law, analyzing its historical origins and assessing current approaches. Notwithstanding the fundamental tenets of international law, including jus cogens and the duty erga omnes, as well as the creation of significant instruments like ICERD, racism persists profoundly within global cultures. The paper examines the reasons for the persistence of implementation gaps despite several treaties and declarations, frequently attributed to states' reluctance to address local racial issues and the constraints of legal definitions. The issues of white racism, global economic disparities, and the enduring impacts of colonialism are examined as persistent obstacles to racial equality. The document evaluates the efficacy of international frameworks, including the CERD and notable declarations such as the Durban Declaration and UNESCO’s initiatives, in addressing racism. Modern international law has the significant difficulty of harmonizing its universal aspirations with the enduring realities of racial hierarchies and inequality. The research emphasizes that addressing racism necessitates not only strong legal frameworks but also aggressive enforcement, comprehensive policy reforms, and intercultural engagement. The international community must consistently evolve and enhance its strategies to fully achieve the promise of universal human rights and racial equality. Keywords: Racism, Elimination, Discrimination, Human Rights, Challenges, Enforcement Implementation, Int. Law